2009
DOI: 10.5210/fm.v14i5.2365
|View full text |Cite
|
Sign up to set email alerts
|

Comparing featured article groups and revision patterns correlations in Wikipedia

Abstract: Collaboratively written by thousands of people, Wikipedia produces entries which are consistent with criteria agreed by Wikipedians and of high quality. This article focuses on Wikipedia’s Featured Articles and shows that not every contribution can be considered as being of equal quality. Two groups of articles are analysed by focusing on the edits distribution and the main editors’ contribution. The research shows how these aspects of the revision patterns can change dependent upon the category to which the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Poderi (2009) investigated the correlation between revision patterns and quality of featured articles of Wikipedia, and found that such correlation is meaningful and having a main author would increase the consistency and quality of Wikipedia articles. Moreover, Jones (2008) investigated the relationship between patterns of editing and article quality on Wikipedia by comparing featured and non-featured articles.…”
Section: Featured Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Poderi (2009) investigated the correlation between revision patterns and quality of featured articles of Wikipedia, and found that such correlation is meaningful and having a main author would increase the consistency and quality of Wikipedia articles. Moreover, Jones (2008) investigated the relationship between patterns of editing and article quality on Wikipedia by comparing featured and non-featured articles.…”
Section: Featured Articlesmentioning
confidence: 99%
“…Lin 2006;Poderi 2009;Muller-Seitz & Reger 2009;Ha & Y.-H. Kim 2009;Pfeil et al 2006;Kaplan & Haenlein 2010;Mattus 2008;de Laat 2010;Yasseri & Kertész 2012;Kimmons 2011). In addition, Wilkinson and Huberman (2007b) is covered by Medelyan et al (2009).…”
Section: Other Collaboration Topicsmentioning
confidence: 99%
“…Other studies have examined factors that led to such articles to be considered as high‐quality articles. Poderi () investigated the relationship between revision patterns and quality of featured articles of Wikipedia. He examined two aspects of revision patterns: edits typology and the editors' distribution.…”
Section: Quality Of Contentmentioning
confidence: 99%
“…Finally, moving down from the level of an entire language project, this kind of analysis might also be done at portal or subject level. [48] does a similar analysis though only on a small subset of article. They obtain counter-intuitive results, as it seems from their analysis that the subject having the more feature articles (high-density subjects in his terminology) have longer articles, but fewer edits and contributors than the lowdensity subjects, while the ratio between major and minor edits is the same in the two groups.…”
Section: B Future Researchmentioning
confidence: 99%